FERGANA MEDICAL INSTITUTE OF PUBLIC HEALTH FACULTY OF PEDIATRICS, DENTISTRY DEPARTMENT STUDENT: TOLKHINJONOVA DURDONA (Лучшие интеллектуальные исследования, 2025)
AbstractThis article analyzes the micro-morphological structure of the main dental tissues—enamel, dentin, cementum, and pulp—their functional importance, and morphological changes occurring with aging. From a microscopic perspective, the cellular and fibrous structure of each tissue, their interrelations, as well as physiological and pathological changes are examined. Additionally, the diagnostic and therapeutic significance of age-related changes is discussed in the context of dental practice. The article holds scientific and practical value for students and professionals in gerontostomatology, therapeutic, and prosthetic dentistry.